2003
DOI: 10.1016/s0014-5793(03)00282-5
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the K+ channel KcsA with membrane phospholipids as studied by ESI mass spectrometry

Abstract: In this study we have used electrospray ionization mass spectrometry (ESI-MS) to investigate interactions between the bacterial K + channel KcsA and membrane phospholipids. KcsA was reconstituted into lipid vesicles of variable lipid composition. These vesicles were directly analyzed by ESI-MS or mixed with tri£uoroethanol (TFE) before analysis. In the resulting mass spectra, non-covalent complexes of KcsA and phospholipids were observed with an interesting lipid speci¢city. The anionic phosphatidylglycerol (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
53
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 24 publications
2
53
0
Order By: Relevance
“…Using the KcsA channel as their model, Demmers et al [ 68 ] investigated the how different lipids interacted with the channel. They reconstituted KcsA channels in liposomal bilayers of different lipid composition, exposed them to a mild solvent, and then employed electrospray mass spectrometry to attempt to identify preferences in non-covalent lipid binding with the protein.…”
Section: Ion Channel-lipid Interactionsmentioning
confidence: 99%
“…Using the KcsA channel as their model, Demmers et al [ 68 ] investigated the how different lipids interacted with the channel. They reconstituted KcsA channels in liposomal bilayers of different lipid composition, exposed them to a mild solvent, and then employed electrospray mass spectrometry to attempt to identify preferences in non-covalent lipid binding with the protein.…”
Section: Ion Channel-lipid Interactionsmentioning
confidence: 99%
“…These simulations are able to provide insights into the nature of the interactions between membrane proteins and their lipid environment [168,[171][172][173][174] and analysis of those crystal structures of membrane proteins that contain lipids provides a detailed structural per-spective on lipid/protein interactions [56,175]. A number of experimental studies have also revealed the importance of bound lipid molecules for the stability and function of some membrane proteins [176][177][178][179][180] For example, in the case of the K + channel KcsA, acidic phospholipids appear to bind to specific (non-annular) sites at which they play a role in refolding and possibly in function [181][182][183]. Examples of recent computational work aiming to understand these interactions are the comparative studies [184,185] of simulations of two integral membrane proteins, representing the two main classes of such protein an α-helical membrane protein (KcsA) vs a β-barrel protein (OmpA) or the comparison of the behaviour of a membrane protein in a lipid bilayer and a detergent micelle environment [186].…”
Section: Protein/lipid Interactionsmentioning
confidence: 99%
“…A further examination of the KcsA crystal structure reveals that it contains noncovalently bound lipid (2,14) identified as phosphatidylglycerol (PG) (15). Tight binding prevents these lipids from dissociating appreciably from the protein by treatments such as detergent solubilization, and indeed, they cocrystallize with the protein and can be seen in the x-ray structure.…”
mentioning
confidence: 99%